The Influence of Communication and Attachment with Peers on Adolescence Character in Rural Area - Zervina Rubyn Devi Situmorang; Dwi - Hastuti; Tin - Herawati (Journal of Child Development Studies, 2016)
Adolescence is a unique phase because at this stage the person becomes more independent, and togetherness intensity with peers increases at this stage. However, adolescent relationships with peers can affect positively or negatively on adolescent characters. This study aimed to analyze the effect of adolescent-peers communication and attachment on adolescent characters. The study was conducted in Pamijahan, Bogor Regency, involving 109 students of Vocational High School (SMK). Data were collected by using a modified instrument of the Parent-Adolescent Communication Scale, Adolescent Attachment Questionnaire and VIA-Youth. Data were processed by using descriptive analysis and regression analysis. The results indicated high communication problem between adolescents and their peers. In addition, that was low openness among adolescents and their peers. The attachment between adolescents and their peers were also found low. The scores of rural adolescents character in this study were relatively low. It was allegedly associated with a low score of communication and attachment with peers. Results of regression analysis showed that only the attachment with peers has a significant effect on the scores of adolescent characters in rural.